Health education as a strategy for encouraging children's vaccination: rapid review - Sousa Neto, Antonio Rosa de; Silva, Ana Rosa Bonfim da; Aranha, Graziella Neiva; Queiroz-Cardoso, Andréia Insabralde de (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Although vaccines have significantly improved the lives of the world's population since their implementation, there has been recent stagnation and, in some cases, even a reversal of previously achieved gains. Aim: To summarize the evidence on how to use health education to encourage the vaccination of children. Outlining: Rapid review, guided by the question "How to use health education to encourage the vaccination of children?" carried out in 2023, using two databases and an electronic library. The searches yielded 2,666 documents, of which 12 articles were selected for data extraction, summarization, and discussion. Results: The community and the home were the main places described for interventions. Fathers, mothers, and guardians/caregivers of children were the audience most mentioned for interventions. Educational instruments, such as booklets, leaflets, and health manuals, were the most used. The most frequent strategies were conventionally transmitting information in the waiting room, teaching during care or home visits, and using or making educational instruments available. Implications: The study clarified how to use health education to encourage the vaccination of children, detailing the intervention locations, the target audience, the necessary instruments, and adequate strategies.